2005
DOI: 10.4049/jimmunol.175.8.5067
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Editing Can Lead to Allelic Inclusion and Development of B Cells That Retain Antibodies Reacting with High Avidity Autoantigens

Abstract: Receptor editing is a major B cell tolerance mechanism that operates by secondary Ig gene rearrangements to change the specificity of autoreactive developing B cells. In the 3-83Igi mouse model, receptor editing operates in every autoreactive anti-H-2Kb B cell, providing a novel receptor without additional cell loss. Despite the efficiency of receptor editing in generating nonautoreactive Ag receptors, we show in this study that this process does not inactivate the autoantibody-encoding gene(s) in every autore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
109
3
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(118 citation statements)
references
References 57 publications
5
109
3
1
Order By: Relevance
“…7). Clearly, alternative explanations for the reduced levels of surface Ig in IgM a B cells may apply, e.g., L chain editing and/or surface Ig downregulation (7,11,26,27).…”
Section: Vh56r؉v 38c Receptors Are Enriched In Marginal Zone (Mz) B Cmentioning
confidence: 99%
See 1 more Smart Citation
“…7). Clearly, alternative explanations for the reduced levels of surface Ig in IgM a B cells may apply, e.g., L chain editing and/or surface Ig downregulation (7,11,26,27).…”
Section: Vh56r؉v 38c Receptors Are Enriched In Marginal Zone (Mz) B Cmentioning
confidence: 99%
“…The autoreactive H/L combination escapes central tolerance and gains access to the periphery because, we presume, the nonautoreactive H/L pair dilutes the expression of the autoreactive pair. Since we discovered this type of partially edited B cell, many examples of allelic or isotypic inclusion have been observed (15,(22)(23)(24)(25), including additional transgenic (Tg)-encoded autoreactivities (26,27) and autoreactivities present within an unperturbed repertoire (11,28). Such B cells have been referred to as ''Trojan horses'' and may, if activated in the periphery, pose a risk of autoimmunity.…”
mentioning
confidence: 99%
“…In fact, it has recently been shown that about half the peripheral mature B cells derived from immature B cells that had undergone receptor editing express two IgL chains [62]. Moreover, several studies have indicated that dual IgL chain expressing auto-reactive immature B cells can escape deletion by being positively selected by the non-auto-reactive IgL and IgH chain combination [63][64][65]. …”
mentioning
confidence: 99%
“…However, and in contrast with this previous report, more than a half of included ͞ B cells showed a mature follicular phenotype (CD23 high ͞CD21 int ) and demonstrated that such cells are not necessarily trapped in the MZ. It has also been hypothesized that dual BCR expression resulted from receptor editing of an autoreactive primary Ig HC͞LC combination (22,23,25,26). In such models of LC inclusion, the expression of multiple antigen receptors was thought to dilute the autoreactive BCR and permit autoreactive cells to escape deletion.…”
Section: Discussionmentioning
confidence: 99%
“…Receptor editing also occurs in normal mice during the selection of immature B cells and may be a major pathway of tolerance induction by rescuing cells with autoreactive BCR from deletion (or anergy) provided that they express a new receptor (20,21). Nevertheless, this editing process intrinsically bears the risk of generating B cell clones that will migrate toward peripheral lymphoid organs while carrying dual or multiple antigen receptors, one of those potentially being autoreactive (22)(23)(24)(25)(26). Moreover, autoreactivity may not be the only way to promote receptor editing because some non-autoreactive knockin mice also showed extensive secondary rearrangements, likely due to a low expression of the knockin gene (27,28).…”
mentioning
confidence: 99%